Correlation between low level of vitamin D [25(OH)D] and high level of interleukin-2 (IL-2) in preterm birth: a systematic review - Sanjaya, I Nyoman Hariyasa Sanjaya; Mulayana, Ryan Saktika Mulyana; I Gusti Ngurah Agung Trisnu Kamajaya (Indonesian Journal of Perinatology, 2024)
Preterm birth, characterized by uterine contractions and cervical changes before 37 weeks of gestation, is a leading cause of neonatal morbidity and mortality worldwide. Its multifactorial pathophysiological mechanisms include inflammatory responses. Emerging evidence suggests that vitamin D and interleukin-2 (IL-2), a pro-inflammatory cytokine, play significant roles in preterm birth by modulating immune responses. A systematic literature review was conducted using Google Scholar and PUBMED databases (2010–2023). Keywords included "vitamin D," "interleukin-2," and "preterm birth." Inclusion criteria covered observational, cohort, and case-control studies investigating the relationship between vitamin D, IL-2, and preterm labor. A total of eight studies met the eligibility criteria and were synthesized narratively. The review revealed that vitamin D deficiency is linked to increased IL-2 levels and heightened inflammatory cytokine activity, contributing to uterine smooth muscle contractions and preterm labor. Conversely, sufficient vitamin D levels suppress IL-2 transcription and reduce pro-inflammatory cytokines, potentially mitigating the risk of preterm birth. However, inconsistencies across studies were observed, attributed to population heterogeneity and varying definitions of preterm birth. Vitamin D may protect against preterm birth by modulating immune responses and reducing inflammation. Incorporating vitamin D supplementation into antenatal care, particularly for at-risk populations, could reduce preterm birth rates. Further randomized controlled trials are necessary to validate these findings and determine optimal supplementation strategies.